Ribbon-like microfiber of vulcanized and non-vulcanized natural rubber obtained by the solution blow spinning - Sousa, Eliraldrin Amorin [UNESP]; Sanches, Alex Otávio [UNESP]; Vilches, José Luiz [UNESP]; da Silva, Michael Jones [UNESP]; de Paula, Fernando Rogério [UNESP]; McMahan, Colleen Marie; Malmonge, José Antonio [UNESP] (Wiley, 2024)
Natural rubber (NR) microfibers were obtained from NR/chloroform solutions with or without vulcanization agents, by a solution blow spinning (SBS) technique. The microfibers showed a ribbon-like morphology with average widths ranging from 15 to 45 μm, depending on the processing conditions. Concentrations of 3%, 4%, and 5% (wt/vol) of NR/chloroform were compared; at 4% wt/vol the spinning process was most stable, and fiber width was the most homogeneous. Microfibrous NR membranes incorporating vulcanizing agents were treated at temperatures of 70, 80, and 90°C for 1, 2, 3, and 4 h. Membrane tensile strength and elongation at break varied with temperature and treatment time. The best result was found with the sample treated at 90°C for 3 h. In this case, the tensile strength and elongation at break was (4.9 ± 0.8) MPa and (867 ± 18) % which is about 310% and 330% higher than the values found for the same sample without the incorporation of vulcanizing agents. This expressive increase was attributed to the vulcanization of the rubber, which also provided a shift to a higher value of the glass transition temperature. Overall properties of the blow-spun films, especially the high elasticity-contraction, suggest they are attractive candidates for use in robotics, and biobased electronics including wearable sensors.
Keywords: natural rubber microfiber; ribbon-like morphology; solution blow spinning; vulcanization